Potensi Teknologi dan Media Sosial Dalam Meningkatkan Pemasaran Produk Asuransi Syariah - Dita Ayu Susmita; Nuri Aslami (VISA: Journal of Vision and Ideas, 2021)
As the largest Muslim country, the country occupied by 236,53 The population is Muslim, if this is used and used as an opportunity for sharia insurance to develop rapidly in this country. Indonesia should have the potential to become the largest Muslim country where most of the Muslim population uses sharia products, especially sharia insurance. In fact, the current fact is that not many Indonesian Muslims use banking and non-banking products on the basis of sharia principles. AAJI's data report, if users of insurance products in Indonesia still reach 7.5%, and only 5% of them are users of sharia insurance. The lack of awareness of knowledge and the lack of strong exposure to sharia insurance products are indicators of the reason why there is still a small level of customer participation using sharia insurance. This reason is further strengthened when viewed from the literacy rate for sharia insurance in Indonesia which has only reached a nominal figure of 19,4%. For this reason, considering the widespread use of social media in Indonesia, which is dominated by the current millennial and generation Z, the marketing strategy of sharia insurance is now starting to move by utilizing the digitalization of marketing media. This study is intended to find out the potential influence of technology and social media in helping to increase sales of sharia insurance products in terms of marketing aspects. Observational analysis of previous research and of sharia insurance companies that carried out this marketing strategy, obtained the findings that social media marketing and the compliance of several insurance products that apply sharia principles in it, are significantly able to increase people's purchasing power or contribute significantly. Indirectly persuade social media users to determine their decision to buy sharia insurance products. Key words : Sharia insurance marketing, Social media, Technology.